Towards Economic diversification by Enhancing Inflow of International Students to Oman (International Journal of Scientific Research and Management (IJSRM), 2022)
The higher education in the GCC region in general and Oman in particular has shown tremendous growth in internationalization of higher education since late 1990s as private universities and colleges were permitted to establish affiliation with foreign universities and higher education institutions (HEIs). The government has been proactively investing in improvising its human capital through higher education. Furthermore, the country enjoys many advantages over other GCC countries with respect to foreign policy, political stability, global competitiveness index and global peace index. Despite its established advantages, the rate of inflow of foreign students is not encouraging. This paper overviews the globalization of higher education in terms of inbound and outbound ratios in the GCC region and attempts to provide an outline for enhancing the inflow of international students to Oman. The inflow of international students will contribute to the economic growth of Oman economy as well.